Teaching conservation-restoration in an art school: sharing experiences - Marie-Hélène Breuil; Muriel Verbeeck (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
Teaching conservation-restoration in an art school can be considered a blessing as well as a challenge: What is the position of a conservator-restorator in this environment? What are the relationships between art conservation and creation, creation and technique? What legitimises research in conservation-restoration, scientific or applied, in this context? This paper, based on our teaching experiences in France and in Belgium reveals a field of expertise and the necessity of understanding the processes of art creation holistically.